Climate change, intergenerational equity and the social discount rate. (November 2014) - Caney, Simon
Climate change is projected to have very severe impacts on future generations. Given this, any adequate response to it has to consider the nature of our obligations to future generations. This paper seeks to do that and to relate this to the way that inter-generational justice is often framed by economic analyses of climate change. To do this the paper considers three kinds of considerations that, it has been argued, should guide the kinds of actions that one generation should take if it is to treat both current and future people equitably. In particular it examines the case for what has been termed pure time discounting, growth discounting and opportunity cost discounting; and it assesses their implications for climate policy. It argues that none of these support the claims of those who think they give us reason to delay aggressive mitigation policies. It also finds, however, that the second kind of argument can, in certain circumstances, provide support for passing on some of the costs of mitigation to future generations.